Genetic parameters estimation on functional dryness traits of crossed black paddy rice "Baas Selem Cultivar X Situ Patenggang” variety - I G P M Aryana; B B Santoso; M Zairin; M Farid (Journal of Degraded and Mining Lands Management, 2014)
The aims of this study were to elucidate heritability and the role of drought traits genes of black paddy rice for determination base of the selection method to obtain drought tolerant and high yield potential of black paddy rice. The study was conducted through two experiments during February-November 2013. The first experiment was the establishment of populations from crosses carried out in the hybridization room. The second trial was evaluation of the genetic diversity of drought properties held in the greenhouse of the Faculty of Agriculture, University of Mataram. Planting was carried out in pots without experiment design. Population of P1 (parental-Situ Patenggang), P2 (parental-Baas Selem) were 50 plants of each; population of F1, F1BC.1.2, and F1BC.1.1 were 25 plants of each, and 250 plants of F2, as well as control of drought susceptible variety (IR20) was 10 plants. To determine the heritability and the role of genes controlling drought traits were used index of bud dry and cure of IRRI standard. The results showed that crossing of black paddy rice "Baas Selem x Situ Patenggang” had relatively moderate heritability in broad sense and low heritability in narrow sense. In the crossed F1 population was found that gene action of drought trait was not perfectly dominant